Photon counting performance of amorphous selenium and its dependence on detector structure - Stavro, Jann (J Med Imaging (Bellingham), 2018)
Photon counting detectors (PCD) have the potential to improve x-ray imaging; however, they are still hindered by high costs and performance limitations. By using amorphous selenium (a-Se), the cost of PCDs can be significantly reduced compared with modern crystalline semiconductors, and enable large-area deposition. We are developing a direct conversion field-shaping multiwell avalanche detector (SWAD) to overcome the limitation of low carrier mobility and low charge conversion gain in a-Se. SWAD’s dual-grid design creates separate nonavalanche interaction (bulk) and avalanche sensing (well) regions, achieving depth-independent avalanche gain. Unipolar time differential (UTD) charge sensing, combined with tunable avalanche gain in the well region allows for fast response and high charge gain. We developed a probability-based numerical simulation to investigate the impact of UTD charge sensing and avalanche gain on the photon counting performance of different a-Se detector configurations. Pulse height spectra (PHS) for 59.5 and 30 keV photons were simulated. We observed excellent agreement between our model and previously published PHS measurements for a planar detector. The energy resolution significantly improved from 33 keV for the planar detector to [Formula: see text] for SWAD. SWAD was found to have a linear response approaching [Formula: see text].